15. Ifa = -8, b = -7, c = 6, then verify that (a + b) + c = a + (b + c).
Attachments:
![](https://hi-static.z-dn.net/files/d26/ac32ff444e0f566c4568ff7c3a4ae556.jpg)
Answers
Answered by
2
Answer:
(-8-7)+6= -8+(-7+6)
-15+6 = -8-1
-9 = -9
therefore LHS=RHS
Answered by
1
Step-by-step explanation:
Given :- a= -8, b= -7, c= 6
To prove :- (a+b)+c = a+(b+c)
Solution :- a+b = -8 + (-7)
= -8 -7
= -15
therefore (a+b)+c = -15+6
= -9 ........(1)
now, (b+c) = -7 + 6
= -1
therefore a+(b+c) = -8 +(-1)
= -8-1
= -9 ..........(2)
from (1) and (2), we get,
(a+b)+c = a+(b+c)
hence proved.
Thank you..
Similar questions